Toward defect‐free semi‐polar GaN templates on pre‐structured sapphire. Issue 5 (12th December 2015) - Han, Yisong; Caliebe, Marian; Hage, Fredrik; Ramasse, Quentin; Pristovsek, Markus; Zhu, Tongtong; Scholz, Ferdinand; Humphreys, Colin
Abstract : The microstructure of semi‐polar (11–22) GaN templates grown on pre‐structured r‐plane sapphire by MOVPE has been characterized by TEM. Cross‐sectional observations indicate that defects are generated in three regions of the layers: threading dislocations at the inclined GaN/sapphire interface, basal plane stacking faults (BSFs) at the c − ‐wing, BSFs and threading dislocations at the coalescence between neighboring GaN stripes. An in situ SiN interlayer deposited at an early stage of the growth is shown to be effective in blocking the propagation of dislocations, which is mainly attributed to SiN formed on the c‐plane rather than on the (11–22) plane. Si‐doped marker layers have been used to study the evolution of the growth front before coalescence as a function of temperature. A high growth temperature is associated with the formation of highly faceted GaN stripes. Dislocations originally running along the c‐direction are bent to the [11–20] direction driven by a progressing (11–22) facet. An efficient defect reduction is realized as a result of terminating these dislocations at voids partially defined by the (11–20) facet.